PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT PADA INSPEKTORAT PROVINSI BALI - Putu Arix Pratiwi; Putu Cita Ayu; Ni Putu Yeni Yuliantari (UNHI Press, 2022)
The first step in ensuring an audit's quality is to plan ahead of time and rely on the expertise and accuracy of those conducting the examination. The Inspectorate of Bali Province was the focus of the investigation, which aimed to determine the impact of competence and independence on audit quality. This study focused on the 34 auditors who work for the Inspectorate of Bali Province. This study used the census method to determine the sample size. The data was analyzed using multiple linear regression analysis. A value of 0.734 indicates that competence and independence account for 73.4 percent of the variation in audit quality. Competence has a significant and positive impact on audit quality. Competence and audit quality go hand-in-hand in Bali Province's Inspectorate of Bali Province. Independent auditors have a significant and positive effect on audit quality. The more independent the Inspectorate of Bali Province is, the better the audits are.